The Potency of Indigenous Lactobacillus farciminis LIPI12-2-LAB033 Isolated from Non-Dairy Product of Indonesian Fermented Food as a New Source of β-galactosidase Enzyme - Setiyoningrum, Fitri; Priadi, Gunawan; Afiati, Fifi; Rohmatussolihat, Rohmatussolihat; Anjani, Aulia Hesti (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
AbstractThe β-galactosidase is an enzyme that plays an essential role in the lactose hydrolysis into glucose and galactose. This study examines the potential of β-galactosidase from several lactic acid bacteria (LAB) isolated from non-dairy products Indonesian fermented foods and purifies them to increase their specific activity. The enzyme was extracted using ultrasonication, purified with ammonium sulfate, and dialyzed with a cellulose membrane (11 kDa). The result of isolates tests showed that Lactobacillus farciminis LIPI12-2-LAB033 had the highest specific activity of 13.9 U/mg protein. Precipitation using 40% ammonium sulfate increased the specific activity up to 19.6 U/mg protein. This enzyme works optimally at a temperature of 40 °C and pH of 7. The specific activity of this enzyme increases to 75.6 U/mg protein after dialysis. The dialysis process purifies the enzyme 5.44 times with a yield of 26.7%. These findings indicate that Lactobacillus farciminis LIPI12-2-LAB033 can be considered as a source of β-galactosidase enzyme production.Keywords: enzyme, β-galactosidase, Lactobacillus farciminis, indigenous, partial purification  Abstrakβ-galaktosidase merupakan enzim yang berperan penting dalam hidrolisis laktosa menjadi glukosa dan galaktosa. Penelitian ini mengkaji potensi β-galaktosidase dari beberapa bakteri asam laktat yang diisolasi dari makanan fermentasi Indonesia yang bukan produk turunan susu dan memurnikannya untuk meningkatkan aktivitas spesifiknya. Enzim diekstraksi dari sel menggunakan ultrasonikasi kemudian dimurnikan dengan amonium sulfat dan didialisis dengan membran selulosa (11 kDa). Hasil uji isolat menunjukkan bahwa Lactobacillus farciminis LIPI12-2-LAB033 memiliki aktivitas spesifik tertinggi sebesar 13.9 U/mg protein. Pengendapan menggunakan ammonium sulfat 40% meningkatkan aktivitas spesifiknya hingga 19.6 U/mg protein. Enzim ini bekerja optimal pada suhu 40 °C dan pH 7. Aktivitas spesifik enzim ini meningkat hingga 75.6 U/mg protein setelah proses dialisis. Proses dialisis memurnikan enzim menjadi 5.44 kali lipat dengan rendemen 26.7%. Temuan ini menunjukkan bahwa Lactobacillus farciminis LIPI12-2-LAB033 dapat dipertimbangkan sebagai sumber produksi enzim β-galaktosidase.Kata kunci: enzim, β-galaktosidase, Lactobacillus farciminis, indigenous, purifikasi sebagian